Utilization of telecommunication optical routes to power fiber-optic polarization sensors - Vyležich, Zdeněk; Kyselák, Martin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
A single-mode telecommunication optical route can be used for reliable power supplies of a remote non-electric temperature fiber-optic polarization sensor, but the optical route, due to many physical factors, affects an immediate state of polarization during the transmission. This negative phenomenon changes the sensitivity of the sensor itself. The thesis proposes two main approaches to solving that problem. The first approach is based on the suitable connection of a depolarizer and linear polarizers. The second approach is based on signal interference, which takes place in a polarization-maintaining fiber coupler. This article also evaluates the advantages and disadvantages of the two approaches and graphically demonstrates the functionality of the fiber-optic sensor, which was tested by applying a container with water of different temperatures. A big advantage of this type of sensor is that it is not necessary to have components, that are dependent on electricity, near the monitored place, where there may be no access to electricity, or the place may be sensitive to an electric charge. Paper demonstrates the possibility of successfully powering the non-electric sensor via a classical optical route.
Optica Applicata, Vol. 52, 2022, nr 4, s. 565-574
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; power supply; optical route; polarization; temperature sensor